Do people demand fact-checked news? Evidence from U.S. Democrats - Felix Anand Chopra; Ingar Haaland; Christopher Roth (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
In a large-scale online experiment with U.S. Democrats, we examine how the demand for a newsletter about an economic relief plan changes when the newsletter content is fact-checked. We first document an overall muted demand for factchecking when the newsletter features stories from an ideologically aligned source, even though fact-checking increases the perceived accuracy of the newsletter. The average impact of fact-checking masks substantial heterogeneity by ideology: fact-checking reduces demand among Democrats with strong ideological views and increases demand among ideologically moderate Democrats. Furthermore, fact-checking increases demand among all Democrats when the newsletter features stories from an ideologically non-aligned source.
Keywords: D83; D91; L82; 330; Fact-checking; News Demand; Information; Media Bias; Belief Polarization